Assessing reasons for decreased primary care access for individuals on prescribed opioids: an audit study. Issue 5 (May 2021) - Lagisetty, Pooja; Macleod, Colin; Thomas, Jennifer; Slat, Stephanie; Kehne, Adrianne; Heisler, Michele; Bohnert, Amy S.B.; Bohnert, Kipling M.
Abstract : Abstract: Many primary care clinics are resistant to accept new patients taking prescription opioids for chronic pain. It is unclear how much of this practice is specific to individuals who may be perceived to have aberrant opioid use. This study sought to determine whether clinics are more or less willing to accept and prescribe opioids to patients depending on whether their history is more or less suggestive of aberrant opioid use by conducting an audit survey of primary care clinics in 9 states from May to July 2019. Simulated patients taking opioids for chronic pain called each clinic twice, giving one of 2 scenarios for needing a new provider: their previous physician had either (1) retired or (2) stopped prescribing opioids for unspecified reasons. Clinic willingness to continue prescribing opioids and accept the patient for general primary care were assessed. Of 452 clinics responding to both scenarios (904 calls), 193 (43%) said their providers would not prescribe opioids in either scenario, 146 (32%) said their providers might prescribe in both, and 113 (25%) responded differently to each scenario. Clinics responding differently had greater odds (odds ratio = 1.83 confidence interval [1.23-2.76]) of willingness to prescribe when the previous doctor retired than when the doctor had stopped prescribing. These findings suggest that primary care access is limited for patients taking opioids for chronic pain, and differentially further reduced for patients whose histories are suggestive of aberrant use. This denial of care could lead to unintended harms such as worsened pain or conversion to illicit substances. Abstract : In a multistate audit, primary care access was limited for patients taking opioids for chronic pain, and differentially further reduced when their histories suggested aberrancy.